Original paper Interstitial brachytherapy for bladder cancer with the aid of laparoscopy* - Klinken, Annemieke Nap-van; Bus, Saskia J.E.A.; Janssen, Theodorus G.; Gellekom, Marion P.R. Van; Smits, Geert; Steen-Banasik, Elzbieta van der (Journal of Contemporary Brachytherapy, 2014)
Since 2009, 40 patients with a T1/T2 bladder cancer have been treated at ARTI with interstitial brachytherapy via laparoscopy. Under general anaesthesia, the tumour area is implanted under cystoscopic control with the aid of a laparoscope, and instruments are attached to the Da Vinci robot. Mapping is then done via a simulator photo and a CT scan. With this method, the patient has fewer complications and the average hospitalization time is halved, while a consistent quality of implant is maintained. This method is also associated with a major reduction in the number of problems that can be attributed to the accessibility of the catheter.